Pollution status of marine protected areas worldwide and the consequent toxic effects are unknown. (December 2018) - Abessa, Denis M.S.; Albuquerque, Heitor C.; Morais, Lucas G.; Araújo, Giuliana S.; Fonseca, Tainá G.; Cruz, Ana C.F.; Campos, Bruno G.; Camargo, Julia B.D.A.; Gusso-Choueri, Paloma K.; Perina, Fernando C.; Choueri, Rodrigo B.; Buruaem, Lucas M.
Abstract: Chemical pollution is considered a factor that may threaten marine protected areas (MPAs), and recent studies have found contamination and associated biological effects in some MPAs. However, organized data on this topic are lacking. This study reviewed the literature on pollution in MPAs in order to compile data, determine whether MPAs are influenced by pollution and, whenever possible, describe how they are being affected by contaminants. The results show that the pollution status is unknown in most MPAs worldwide. When any information is available, it is often insufficient to diagnose the threats to biodiversity or to support further actions. More robust and extensive information is available on a small number of MPAs, and much less information is available regarding the negative effects of pollution. More than 80% of the areas studied exhibited evidence of contamination at potentially toxic concentrations or were found to have a status that produced toxic effects on the biota. The scientific community is encouraged to study pollution in MPAs worldwide. Graphical abstract: The icons 1–6 and 8 were freely downloaded from Integration and Application Network, University of Maryland Center for Environmental Science (ian.umces.edu/imagelibrary/ ). 1- Jane Hawkey; 2- Diana Kleine; 3, 4, 8- Tracey Saxby; 5- Dieter Tracy; 6- Alexandra Fries. Icon 7 was downloaded from pixabay, (https://pixabay.com ), with no attributions required. Image 1 Highlights: Pollution information is available for only 67 of 13, 674 MPAs worldwide. More than 50% of the MPAs studied present any sign of contamination. None of the MPAs studied has an extensive and varied chemical profile. Pollution in MPAs worldwide has been underestimated. More research on pollution in MPAs is urgently required. Abstract : Levels of pollutants and their toxic effects are unknown for the most of MPAs worldwide. Existing data on few MPAs indicate that pollution is a concerning issue.